Risk Factors and Ergonomic Influence on Musculoskeletal Disorders in the Work Environment - Kamijantono, Harry; Sebayang, Moriko Madadoni; Lesmana, Andrean (Newinera Publisher, 2024)
Musculoskeletal disorders (MSDs) are medical conditions that affect the muscles, bones, ligaments, tendons, nerves and other supporting structures in the human body. This research aims to identify and analyze risk factors and the influence of ergonomics on musculoskeletal disorders in the work environment. Using qualitative methods based on literature review studies, this research explores various factors that contribute to musculoskeletal disorders through content analysis from various previously published literature sources. The main risk factors contributing to this disorder include unergonomic work postures, lifting heavy loads, and repetitive movements. This research highlights the importance of ergonomic interventions, such as adjusting sitting position, setting up work tools, and ergonomics training for workers, in reducing the risk of musculoskeletal disorders. It is hoped that the results of this research will provide useful insights for occupational health practitioners, human resource managers, and policy makers in designing and implementing effective ergonomics programs in the workplace. By understanding risk factors and effective ergonomic interventions, companies can improve worker health and well-being, reduce the incidence of musculoskeletal disorders, and ultimately increase work productivity and efficiency.